2021
DOI: 10.1111/cas.15024
|View full text |Cite
|
Sign up to set email alerts
|

Combining MGMT promoter pyrosequencing and protein expression to optimize prognosis stratification in glioblastoma

Abstract: Pyrosequencing (PSQ) represents the golden standard for MGMT promoter status determination. Binary interpretation of results based on the threshold from the average of several CpGs tested would neglect the existence of the “gray zone”. How to define the gray zone and reclassify patients in this subgroup remains to be elucidated. A consecutive cohort of 312 primary glioblastoma patients were enrolled. CpGs 74‐81 in the promoter region of MGMT were tested by PSQ and the protein expression was assessed by immunoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…There have been 11 cases, including our two, describing both TMZ treatment outcomes and the degree of MGMT expression, in aggressive or malignant somatotroph tumors; the summary of these cases is shown in Table 1 ( 9 , 10 , 19 22 ). Several previous studies showed the correlation between MGMT promoter methylation and protein expressions in IHC ( 23 , 24 ), and it is thought that unmethylated MGMT promotor most leads to strong expressions in IHC ( 23 , 24 ). Two cases which analyzed the promoter methylation status reported unmethylated MGMT promoters ( 20 , 22 ); and nine cases reported strong expression of MGMT.…”
Section: Discussionmentioning
confidence: 97%
“…There have been 11 cases, including our two, describing both TMZ treatment outcomes and the degree of MGMT expression, in aggressive or malignant somatotroph tumors; the summary of these cases is shown in Table 1 ( 9 , 10 , 19 22 ). Several previous studies showed the correlation between MGMT promoter methylation and protein expressions in IHC ( 23 , 24 ), and it is thought that unmethylated MGMT promotor most leads to strong expressions in IHC ( 23 , 24 ). Two cases which analyzed the promoter methylation status reported unmethylated MGMT promoters ( 20 , 22 ); and nine cases reported strong expression of MGMT.…”
Section: Discussionmentioning
confidence: 97%
“…USN is relatively common and has many causes, including neurodegenerative diseases, neoplasm, aneurysm, traumatic brain injury after the surgical resection of a brain tumour and stroke, where stroke is by far the most prevalent cause [4,[12][13][14]. Left-sided neglect is more common than right-sided neglect, as it is mostly linked to damage to the right hemisphere of the brain [15,16].…”
Section: Classification Of Spatial Neglectmentioning
confidence: 99%
“…The 1p/19q codeletion, 7+/10-, epidermal growth factor receptor (EGFR) amplification status were determined by fluorescence in situ hybridization (FISH). For IDH1 R132 and IDH2 R172 mutations, telomerase reverse transcriptase (TERT) promoter C228T/C250T mutation was tested by Sanger sequencing (18,19). The status of O 6 -methylguanine-DNA methyltransferase (MGMT) promoter was determined by pyrosequencing, and patients were divided into methylated and unmethylated by the average methylation level of 12% (20).…”
Section: Molecular Informationmentioning
confidence: 99%
“…We also employed the principles of RANO for low-grade glioma to evaluate the dynamic change of T2/FLAIR of this GBM cohort (21). MR spectrum (MRS), perfusion-weighted MRI (PWI) by dynamic susceptibility contrast (DSC), and 18 F-FDG-PET MRI were available to some but not all patients during the follow-up to provide valuable information to distinguish treatment response (pseudoprogression and radiation necrosis) from true progression.…”
Section: Treatment and Follow-upmentioning
confidence: 99%